Breeding of the black and red Mesoamerican beans for Central America and the Caribbean. - Rosas, Juan C. (2006)
Bean production in Central America is mainly a small farm operation on hillside, marginal areas, limited by several biotic and abiotic constraints. More than 350,000 t of beans are produced in nearly 0.5 millions of hectáreas, with a rather low yield average of 678 kg/ha. The majority of bean producers utilize low inputs and few farms are mechanized. Autoconsumption is rather high; however, a great portion of the beans is sold by intermediaries. In Honduras, beans are the 7th most important crop in economic value, and has the highest economic return among corn, rice and sorghum. The major market classes in Central America are small red and black (race Mesoamerican) beans. Improvement of these bean types is focused in developing resistance to diseases (common mosaic, golden mosaic, anthracnose, angular leaf spot, rust, web blight, and common bacterial blight) and pests (mainly pod weevil); and tolerance to low fertility, drought and heat. Appropriate hybridization and selection programs are utilized for developing multiple resistant, high yielding, well adapted and commercially accepted cultivars. A broad genetic base is accomplished by using Andean and Mesoamerican sources of germplasm in the hybridization stage. Simultaneous selection for various traits and multilocation testing of advanced lines are practiced. Yield and adaptation nurseries and trials of improved lines are distributed to Central America, Mexico, Panama and Caribbean countries. Testing of advanced lines and on-farm validation and varietal release, are carried out by National Bean Programs and institutions, members of the PROFRIJOL regional program, in collaboration with Zamorano, CIAT and the Bean/Cowpea CRSP.